2002
DOI: 10.1006/jfbi.2002.2012
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the carbon isotope composition of Semaprochilodus insignis, a detritivorous fish associated with oligotrophic and eutrophic Amazonian rivers

Abstract: The Amazonian freshwater fish, Semaprochilodus insignis, varies in carbon isotopic composition during residence in different habitats within its home range. The results indicate that carbon produced in black-water systems contributes to fish stocks harvested from white-water systems, and S. insignis populations in the Central Amazonia are more integrated than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
2
11
0
3
Order By: Relevance
“…Finally, we found that C 4 macrophytes had d 13 C and d 15 N signatures well separated from the other sources (-12.6 ± 1.6, 7.3 ± 0.6, respectively). These values were similar to those found by other stable isotope studies in the Amazonian aquatic system (Araujo-Lima et al, 1986;Benedicto-Cecilio et al, 2000;Leite et al, 2002;Benedicto-Cecilio & Araujo-Lima, 2002;Oliveira et al, 2006), and other neotropical aquatic systems (Hamilton et al, 1992;Lewis et al, 2001;Jepsen & Winemiller, 2007). The d 13 C values of C 3 macrophytes and periphyton samples were also within the range of those published in previous studies (Benedicto-Cecilio et al.…”
Section: Sourcessupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, we found that C 4 macrophytes had d 13 C and d 15 N signatures well separated from the other sources (-12.6 ± 1.6, 7.3 ± 0.6, respectively). These values were similar to those found by other stable isotope studies in the Amazonian aquatic system (Araujo-Lima et al, 1986;Benedicto-Cecilio et al, 2000;Leite et al, 2002;Benedicto-Cecilio & Araujo-Lima, 2002;Oliveira et al, 2006), and other neotropical aquatic systems (Hamilton et al, 1992;Lewis et al, 2001;Jepsen & Winemiller, 2007). The d 13 C values of C 3 macrophytes and periphyton samples were also within the range of those published in previous studies (Benedicto-Cecilio et al.…”
Section: Sourcessupporting
confidence: 91%
“…The d 13 C values of C 3 macrophytes and periphyton samples were also within the range of those published in previous studies (Benedicto-Cecilio et al. 2000;Benedicto-Cecilio & Araujo-Lima, 2002;Manetta et al, 2003) (Table 4).…”
Section: Sourcessupporting
confidence: 77%
See 1 more Smart Citation
“…In fact, POC d 13 C values might have been related to the composition of more positive sources (periphytic algae) in the Paran´a River and more negative values in the phytoplankton, periphyton and riparian vegetation in the Ba´ıa subsystem. Benedito-Cecilio & Ara´ujo-Lima (2002) also found isotopic spatial differences in a detrital fish, Semaprochilodus insignis (Jardine & Schomburgk, 1841), between the oligotrophic and eutrophic parts of the Amazon River associated with spatial isotopic variation in detrital aggregates, the principal source used by this fish. Although C 4 plants are not common (low density and number of species), the C 4 carbon contribution to P. lineatus cannot be discounted along the upper Paran´a River, including the extensions of the Itaipu Reservoir and the floodplain.…”
Section: Discussionmentioning
confidence: 91%
“…It is the same with Central Amazon floodplains where phytoplankton represents a great part of the carbon content of the main species of commercial fish, both in adult (Forsberg et al, 1993;Benedito-Cecilio et al, 2002) and larval stages (Leite et al, 2002) despite making up only 2 % of the regional primary production (Melack and Forsberg, 2001). Thus, phytoplankton is a key element in the food chain of the fishing industry, and since fish is the main source of protein of the riverine population (Santos et al, 2006), the study of phytoplankton is critical to regional development.…”
Section: Introductionmentioning
confidence: 86%